ANALISIS PERBANDINGAN KINERJA KEUANGAN PT TELKOM INDONESIA (PERSERO) TBK SEBELUM DAN SELAMA PANDEMI COVID-19 DIUKUR BERDASARKAN RASIO GROSS PROFIT MARGIN, CURRENT RATIO, TOTAL ASSET TURNOVER, DEBT TO ASSET RATIO DAN PERTUMBUHAN LABA - Septriana, Dani; Rapini, Titi; Abrianto, Tegoeh Hari (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study was conducted to analyze the comparison of financial performance for the period before (2017, 2018, 2019) and during (2020, 2021, 2022) of the coronavirus pandemic at PT Telkom Indonesia Tbk measured by gross profit margin ratio (GPM), current ratio (CR), total asset turnover ratio (TATO), debt to asset ratio (DAR) and profit growth. The financial statements of PT Telkom Indonesia Tbk that have been audited by a public accounting firm are used as a research population. The research sample in the form of a statement of financial position and income statement of PT Telkom Indonesia (Persero) Tbk was listed on the Indonesia Stock Exchange for 6 periods, namely 2017 to 2022. The research methodology uses paired sample t-test with the help of Statistical Product and Service solution (SPSS) software version 24 to support the research data processing process. Data testing in the paired sample t-test found that there was no difference in financial performance both before and during the Covid-19 pandemic at PT Telkom Indonesia (Persero) Tbk as measured using gross profit margin ratio (GPM), current ratio (CR), debt to asset ratio (DAR) and profit growth. However, there are differences in financial performance before and during the coronavirus pandemic as measured by the total asset turnover ratio (TATO).